1982
DOI: 10.1104/pp.70.5.1283
|View full text |Cite
|
Sign up to set email alerts
|

Isoxazolin-5-ones and Amino Acids in Root Exudates of Pea and Sweet Pea Seedlings

Abstract: Seeds of Pisum sativum L. cv Finale and Lathyrs odoratus L. cv Spencer were germinated asepticafly in moistened sand in the dark. At several stages, the amino acid composition of the exudate and of the corresponding roots was analyzed. A number of common amino acids, including homoserine, were exuded by the growing seeding root in an early stage and were partly reabsorbed later. A number of uncommon amino acids, including several isoxazolin-5-one derivatives, uracil alanines, ia-yglutamyl-D-alanine, and a-amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 22 publications
1
12
1
Order By: Relevance
“…These findings clearly indicate that 2-CEIX is a major nitrogenous compound in sweet pea. The contents of 2-CEIX were much higher in these organs than in roots as reported by Kuo et al (1982). The contents of 2-CEIX in the stem and leaves were much higher in the present study than in those reported by Ikegami et al (1984).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…These findings clearly indicate that 2-CEIX is a major nitrogenous compound in sweet pea. The contents of 2-CEIX were much higher in these organs than in roots as reported by Kuo et al (1982). The contents of 2-CEIX in the stem and leaves were much higher in the present study than in those reported by Ikegami et al (1984).…”
Section: Discussioncontrasting
confidence: 56%
“…Among compounds, which have been reported to be much contained in sweet pea, 2-CEIX (Kuo et al, 1982) has the coincided molecular composition (Fig. 1B), and all NMR spectra were assigned to 1 H and 13 C of this compound, resulting in the identification.…”
Section: Ci-ms and Esims Analyses Gave [M + H]mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been reported that trigonelline is present in root exudates of legumes (20,23). The concomitant presence of trigonelline in the host plant and of the corresponding catabolic genes in the symbiotic bacterium suggests that trigonelline could be used as a nutrient by Rhizobium strains during rhizosphere colonization and/or plant infection.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of the trc genes on the same replicon, in a region closely surrounded by symbiosis genes, suggests some relationship between trigonelline catabolism and symbiosis. It is noteworthy that the genes controlling the catabolism of homoserine, which is a secondary metabolite of legumes (23), are similarly located on the pSym plasmid (21). In contrast, the genes controlling the catabolism of calystegines, which are secondary metabolites of nonlegumes, are located on a plasmid not essential for symbiosis (6,41).…”
Section: Resultsmentioning
confidence: 99%